Enabling equitable collective action and policy change for poverty reduction and improved natural resource management in the Eastern African highlands - German, L.; Ayele, Seife; Tanui, J.; Nyangas, S.; Taye, H.; Admassu, Z.; Mazengia, W.; Tirwomwe, W.; Begashaw, L.; Tsegaye, M.; Alinyo, F.; Mekonnen, A.; et al. (International Food Policy Research Institute, 2008)
The role of local and external institutions in natural resource management (NRM) is gaining attention in the literature, fostering greater understanding of the relationship between collective action and poverty, collective action and equity, and the conditions under which collective action institutions take root. It has also led to increased understanding of how uncritical practices by external development institutions can propagate social inequities in NRM. Yet little research has been conducted to understand how to foster local collective action institutions where they are absent, or to improve institutional practice. This research integrates empirical and action research in an effort to generate ‘working solutions’ to problems facing rural communities in their efforts to manage their natural resources in the highlands of Ethiopia and Uganda. Following a brief introduction to the literature and the research, findings are presented according to two distinct phases of research. Data are first presented on existing forms of collective action, the influence of local and external institutions on economic development, and NRM problems that persist despite their negative livelihood consequences. Action research themes selected from a list of identified problems are then presented in greater detail, with lessons learnt thus far in attempting to overcome institutional barriers to improved NRM. The paper concludes with a discussion of the implications of findings for research, institutional practice, and policy.